The use of authorial stance among Arab postgraduate students in thesis writing at Universiti Sultan Zainal Abidin - Alia, Mohammad Merey
Many studies on academic writing in English have focused on the use of stance, particularly in linguistic-based writing research. Taking an assertive stance towards the research being reviewed or reported is considered a challenging task for second language writers. Although many studies have explored stance taking, few of them have focused on the analysis of metadiscourse using the Systemic Functional Linguistic (SFL) approach. Tn addition, few studies have investigated the use of stance taking in the thesis writing of Arab postgraduate students studying at Malaysian universities, particularly at Universiti Sultan Zainal Abidin (UniSZA). Based on the gap, this study purports to investigate the use of stance taking in the introductory chapters of Arab postgraduates' theses employing SFL approach at UniSZA. In this qualitative case study design, data were gathered qualitatively based on the documented 22 introductory chapters of doctoral and master theses, as well as interview responses from six participants, out of the 22 postgraduate students. The sample data were purposively selected from the doctoral and master theses of postgraduate students in several faculties at UniSZA. The theses were conducted in the fields of social science and pure science. The writers' stance taking were analysed using the SFL approach, while interview responses were analysed manually in theme. The findings showed frequent and different use of finite modal operators, less and different use of adjuncts expressing modalisation and other purposes, and less frequent use of comment adjuncts and subjective, rather than objective orientation of the soft and hard domains. The findings revealed that many participants showed unfamiliarity with the use of modality markers and appropriate social and linguistic conventions, which are suitable for each community. Four main themes emerged pertaining to stance and academic writing challenges, which are adopting stance challenges, language difficulties, L1 transfer, and attitude towards writing. The study concluded that stance taking is very important to be explicitly taught to postgraduate students to enrich the quality of thesis writing. This study is significant as useful resources for academic writing instructors, supervisors and academic writers. In addition, it can expand the existing body of literature on stance taking and academic writing challenges faced by EFL writers in general and Arab postgraduates in particular. Extensive research should be done to explore the use of SFL approach in the meta discourse analysis of stance taking in international postgraduate students' theses in Malaysia.